TEOR DE N, PEK NO FRUTO DA LARANJEIRA BAIANINHA, INFLUENCIADO PELA ADUBAÇÃO MINERAL - Moreira, C. S.; Lucchesi, A. A.; Barbin, D. (REVISTA DE AGRICULTURA, 2016)
TEOR DE N, PEK NO FRUTO DA LARANJEIRA BAIANINHA, INFLUENCIADO PELA ADUBAÇÃO MINERAL